ANALISIS FAKTOR YANG MEMPENGARUHI ALIH FUNGSI KOMODITI KARET MENJADI KOMODITI TEBU DI DESA KARYA MAKMUR KECAMATAN BELITANG JAYA KABUPATEN OKU TIMUR (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2020)
Since the beginning of development, there is no doubt about the role of the agricultural sector in Indonesia's development. The development of the agricultural sector is directed at increasing the productivity of agricultural products in order to meet the food needs of the community and the needs of domestic industry, increase exports, increase farmers' income, expand employment opportunities and encourage business opportunities. The plantation sector in East OKU is a sector that is not dominant but plays a major role in the regional economy. The magnitude of the role of the plantation sector is seen from economic variables, namely its contribution to GRDP, employment and availability of natural resources. The plantation sub-sector in East OKU Regency with three main commodities of rubber, oil palm and sugar cane. Rubber is a potential commodity that plays an important role as a source of foreign exchange revenue, absorption of labor, driving economic growth in new centers in the area around plantations and environmental preservation. The reduction of rubber plantation land to sugar cane plantation in Belitang Jaya District where in 2016 the rubber plantation area was 6,298 ha, while in 2018 the area of rubber land in Belitang Jaya District became 5,964 ha resulting in a reduction of land by 5.3% in three years . Karya Makmur Village is one of the villages in the Belitang Jaya Subdistrict, East OKU Regency, which has the largest area in transferring land functions from rubber to sugarcane with an area of 58 hectares. Keywords: Commodity Function Change, Land Reduction, Income.